Uniform Crime Reports (United States): Supplementary Homicide Reports, 1976-1998 - Fox, James Alan ([Verlag nicht ermittelbar], 2000)
These data provide incident-level information on criminal homicides including location, circumstances, and method of offense, as well as demographic characteristics of victims and perpetrators and the relationship between the two. The data were provided monthly to the Federal Bureau of Investigation (FBI) by local law enforcement agencies participating in the FBI's Uniform Crime Reporting Program.